MIKROENKAPSULASI d-LIMONEN UNTUK PERISAAN PRODUK EKSTRUSI - Sri Yuliani, Peter J. Torley dan Bhesh Bhandari (Department of Agroindustrial Technology, Bogor Agricultural University, 2007)
ABSTRACTThe objectives of this research are to determine the effect of microencapsulation on d-limonene retention in starch extrudates and the effect of incorporating encapsulated d-limonene on extruder operation and extrudate properties. Two set of extrusion experiments were carried out in a twin screw extruder (16 mm diameter screw; 40:1 L/D ratio) using corn starch as a food matrix. In one set of experiments, d-limonene was encapsulated in -cyclodextrin. In the other experiments, d-limonene was encapsulated with sodium caseinate. Using a Central Composite Design, three variables were studied: level of encapsulated d-limonene in the feed material, extruder screw speeds and barrel temperatures. Another set of experiment with unencapsulated d-limonene was also performed. Measured parameters included extruder operation parameters (torque and die melt pressure), extrudate properties (expansion ratio and hardness) and d-limonene retention. All variables contributed significantly to the d-limonene retention and extrudate properties. -Cyclodextrin capsules gave higher d-limonene retention (average of 92.2%) than the sodium caseinate capsules (67.5%). A higher expansion ratio was observed from the extrudates containing sodium caseinate capsules than those with -cyclodextrin (average of 1.87 and 1.38, respectively). Extrudates containing -cyclodextrin capsules had a lower hardness (average of 1.14 N/mm2) than those with sodium caseinate capsules (average 2.34 N/mm2). Without encapsulation, retention of d-limonene was the lowest (average of 8.0%), extrudate hardness was the highest (average of 3.38 N/mm2) but expansion ratio was the highest (average of 2.1). Keywords : flavour, microencapsulation, extrusion, d-limonene, -cyclodextrin, sodium caseinate, expansion, texture